Diffraction Wave Attributes to Identify Small-Scale Geological Bodies. (27th June 2022) - Shu, Mengcheng
Abstract : Aiming at the difficulties in the fine description of small- and medium-scale geological bodies in storage, this paper develops a method for describing geological bodies using diffracted wave data and systematically explains the effectiveness of the method through model calculations. Finally, this method is applied to fractures. In the fine description of the type of reservoir and the intrusive rock mass of the reservoir, two diffraction wave attribute analysis methods are used to achieve the fine description of the distribution law of the above small-scale geological bodies. The principal component analysis method is proposed to extract the diffraction from the seismic wave field. Information, the wave field is separated through the kinematics and dynamics of the diffraction wave, and the obtained diffraction wave field better reflects the distribution law of small-scale geological bodies. Verified by examples, the diffraction wave analysis method can be more refined and a comprehensive description of the distribution of small-scale geological bodies.